Onomastics and Branding for Culinary Tourism: Evidence Soto Traditional Culinary - Wiyana, Tri; Bendesa, IKG; Tomahuw, Roberto (Jurnal Penelitian Pariwisata, 2021)
Soto is a traditional culinary dish that is one of Indonesian specialties whose ingredients consist mainly of meat, and vegetable broth. Every region in Indonesia has soto with different characteristics. This study aimed to research the extent to which the naming pattern, the consumer perceives the brand and how much it effects of sales culinary business culinary business in Delanggu District, Klaten Regency, Central Java, Indonesia. Respondents consisted of culinary soto traders and customer perception. Research methodology with qualitative methods by analyzing the naming of the identity of the place of business (onomastic). The next analysis is to integrate branding strategy in developing culinary business. The results of the study showed that the creative branding model for traditional culinary soto, which is how the behavior for making it, the presentation culinary model, and branding with identical names of the people who make it. This research provides an overview of the pattern of branding strategies for culinary endeavors. Culinary entrepreneurs must strive to attract customers with creative models and not ignore local wisdom from the region. Keywords: Traditional Culinary, Culinary Linguistics, Culinary Branding, Soto